On the generalized Krätzel transform and its extension to Boehmian spaces - Al-Omari, Shrideh Khalaf Qasem; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
We investigate the Kratzel transform on certain class of generalized functions. We propose operations that lead to the construction of desired spaces of generalized functions. The Krätzel transform is extended and some of its properties are obtained.